Bandwidth Constrained Multipath Routing Protocol for QoS Provision in MANETs - Balhara, Surjeet; Bhardwaj, Priyanka (Discoveries in Agriculture and Food Sciences, 2017)
Mobile Ad hoc NETworks (MANETs) are composed of mobile nodes with limited resources and unpredictable node movement. With the on-going evolution in MANETs, provision of Quality of Service (QoS) has become a challenging task. In this paper, a node disjoint Bandwidth Constrained Multipath Routing (BCMR) protocol is proposed which considers bandwidth as the key factor to discover multiple paths for QoS provisioning. BCMR accommodates required bandwidth function in flooding route request packets. Extensive simulation study is carried out to investigate the performance of BCMR. Simulation results reveal that BCMR significantly reduces overheads, minimizes overall end to end delay and significantly improves packet delivery ratio.